Chelation-assisted Pd-catalysed ortho-selective oxidative C–H/C–H cross-coupling of aromatic carboxylic acids with arenes and intramolecular Friedel–Crafts acylation: one-pot formation of fluorenones. Issue 18 (10th February 2016) - Sun, Denan; Li, Bijin; Lan, Jingbo; Huang, Quan; You, Jingsong
Abstract : Starting from the readily available substrates, an efficient method for the synthesis of fluorenone derivatives has been developed. Abstract : Pd-Catalysed ortho -selective oxidative C–H/C–H cross-coupling of aromatic carboxylic acids with arenes and subsequent intramolecular Friedel–Crafts acylation has been accomplished for the first time through a chelation-assisted C–H activation strategy. Starting from the readily available substrates, a variety of fluorenone derivatives are obtained in one pot. The direct use of naturally occurring carboxylic acid functionalities as directing groups avoids unnecessary steps for installation and removal of an extra directing group.